Characteristics of state prescription drug monitoring programs: a state‐by‐state survey. Issue 7 (8th April 2016) - Manasco, A. Travis; Griggs, Christopher; Leeds, Rebecca; Langlois, Breanne K.; Breaud, Alan H; Mitchell, Patricia M.; Weiner, Scott G.
Abstract : Objectives: Prescription drug monitoring programs (PDMPs) are state‐based data collection systems recording controlled substance medications. Currently, 49 states have PDMPs. There are discrepancies in reporting patterns, infrastructure, and oversight between programs. We characterized aspects of each state's PDMP. Methods: A web search of each state's PDMP was conducted, and a list of all PDMP administrators was obtained. From August 1 to November 31, 2014, a link to a web‐based survey was sent to each PDMP administrator. Closed‐ended questions included type of access, mandatory‐use programs, data sharing, proactive contact with patients or health care providers, details of pharmacy reporting, and protocols for identifying "high‐risk" patients. Descriptive statistics were used for analysis. Results: We received a 100% response rate (49/49). Ninety‐six percent (47/49) have a physician‐accessible PDMP. Most, 68% (32/49), do not have an enrollment mandate for physicians. Prior to prescribing controlled medications, 16% (8/49) require prescribers to access their state's PDMP. More than half of states (53%, 26/49) reported patient prescriptions over the past two or more years. Most, 57% (28/59), reported a lag time of 1 week or longer for patients to appear in a PDMP database after prescription filling. A majority of states (65% 32/49) share data with at least one other state. Protocols exist to identify high‐risk patients for prescription drug misuse in 55% (27/49) of states. Conclusion: Characteristics of PDMPs are heterogeneous throughout the country. Standardizing data capture, availability, and reporting would improve their usefulness for providers. Copyright © 2016 John Wiley & Sons, Ltd.